Virtues for the people : aspects of Plutarchan ethics - Roskam, Geert; Stockt, L. Van der (Plutarchea hypomnemata., 2011)
Plutarch of Chaeronea, Platonist, polymath, and prolific writer, was by no means an armchair philosopher. He believed in the necessity for a philosopher to affect the lives of his fellow citizens. That urge inspired many of his writings to meet what he considered people''s true needs. Although these writings on practical ethics illustrate in various ways Plutarch''s authorial talents and raise many challenging questions (regarding their overall structure, content, purpose, and underlying philosophical and social presuppositions), they have attracted only limited scholarly attention. Virtues fo.